Identitete kot jih pišejo življenjske zgodbe izseljencev - Čebulj-Sajko, Breda (Traditiones (Ljubljana), 1997)
The paper deals with the theoretical definitions of the concepts of autobiography and identity. Drawing on her field work among Slovene immigrantsin Australia, the author shows the significance of autobiographical testimonies for recognizing the manifestations of a split ethnic identity in this particular immigrant community.
Keywords: slovenski izseljenci; narodna identiteta; avtobiografije; Australia; Avstralija